Features of aggression adolescents with experiences of violence by peers - Fourmanov, Igor A.; Kupchenko, Victoria E. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The paper theoretically analyzes the phenomenon of violence in schools, its main types are described, disclosed the concept of «victimization», reveals personality traits of children exposed to systematic violence by their peers. An empirical study investigates adolescents experience violence at school by their peers, describes the features of adolescent aggression, varying degrees, experiencing violence from their peers at school. It was found that adolescents who experience violence from their peers have lower rates of physical aggression, higher rates of indirect aggression, suspiciousness, hostility, comparedwith adolescents with a low degree of victimization.
Keywords: bullying; victimization; experience violence at school; the aggression of victim